Expression of gag-CA Gene of Jembrana Disease Virus with Cationic Liposomal and Chitosan Nanoparticle Delivery Systems as DNA Vaccine Candidates - Lalu Unsunnidhal; Januar Ishak; Asmarani Kusumawati (Tropical Life Sciences Research, 2019)
One of the obstacles in increasing the population of Bali cattle is the presence of infectious diseases called Jembrana disease that attacks only Bali cattle. This disease is caused by Jembrana Disease Virus (JDV). A prevention method has been introduced; A DNA vaccine candidate was developed by inserting the gag-CA JDV gene in the pEGFP-C1 vector and a delivery system using cationic liposomes and chitosan nanoparticles, which is an important factor in the success of DNA vaccines in inducing immunity. The purpose of this study was to know the expression of the gag-CA gene with these delivery systems and the effectiveness of each delivery system. The expression of the gag-CA gene was tested using HeLa cells. The gag-CA gene JDV has been optimised using codon and inserted in pEGFP-C1. Then, the recombinant DNA was cloned using the E. coli DH5? host. The improvement result was confirmed using polymerase chain reaction (PCR), restriction analysis and sequencing. Recombinant DNA plasmids have been isolated and formulated with cationic liposomes and chitosan nanoparticles. The best characterization of encapsulation with gel inhibition test was chitosan nanoparticles with ratio mass of DNA with chitosan 1:2, diameter size about 178.0 nm and zeta potential +22.5 mV from the measurement using Particle Size Analyzer, while cationic liposome complex was prepared using commercial reagents. The expression results were analysed using fluorescence observation, Two-Step RT-PCR followed by Real-Time PCR analysis and Western Blot. The results showed the design of recombinant DNA plasmids with cationic liposomal and chitosan nanoparticle delivery systems expressing the gag-CA gene JDV. This is evidenced by the proliferation of EGFP-Capsid fusion proteins in HeLa cells and Normalised Expression in Real Time PCR, i.e. 5.36029 for cationic liposome conducting system and 0.00533 for chitosan nanoparticle delivery system. Also a positive band was also obtained with cationic liposomal delivery system on Western blot.